Role of Collaborative Learning for Developing Speaking Skills of Secondary Level Students - Rai, Himan (Gipan, 2024)
Collaborative learning is an engaged learning of the students in which two or more students work together for the same purpose. However, research on the role of collaborative learning in developing language skills of the students have not been taken in a greater extent in the context of school education. In this regard, the present study aims to explore the role of collaborative learning for developing speaking skill of secondary level students and to examine the collaborative learning culture among the secondary level students. Keeping the objectives into consideration, forty secondary level students were selected as the sample by using purposive non-random sample strategy. The data, which was collected by using close ended questionnaires, analyzed and interpreted descriptively. The results of the study show that collaborative learning has constructive role for developing students’ language skills, social skills and personal skills. In the opinion of the students, collaborative learning engaged them in meaningful interaction. Though the students realized the constructive role of collaborative learning, they had a little practice of collaborative learning. They had group discussion to solve problem, peer work and some collaborative projects as the part of collaborative learning practices.